A Qualitative Evaluation of an Experiment on the Application of Active Methodologies in Teaching Software Process Improvement - Colares, Adolfo Francesco de Oliveira; Oliveira, Sandro Ronaldo Bezerra; Furtado, Julio Cezar Costa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
This paper presents a qualitative evaluation of an experiment involving the application of active methodologies to the teaching of Software Process Improvement (SPI). Recognizing that many academic courses cover SPI theoretically but inadequately prepare students for real-world challenges in the software industry, this work proposes the application and qualitative evaluation of a curriculum structured around active methodologies. The study is grounded in widely recognized models, such as the Capability Maturity Model Integration (CMMI) and the Brazilian Software Process Improvement Reference Model (MR-MPS-SW). The methodology used involved three main stages: mapping the essential SPI knowledge assets, conducting expert interviews, and peer review to validate the developed materials. An experiment was conducted with two groups of students to compare traditional teaching approaches with the proposed active methodologies. The qualitative results showed an expected improved performance in the experimental group, highlighting an improved ability to apply concepts in practice. Despite limitations such as the absence of subsequent evaluations in real professional settings and the requirement for continuous content updates, the study suggests that adopting active methodologies can effectively develop practical competencies that are crucial for future professionals.